2013
DOI: 10.2528/pierb12100803
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Coupling in Longitudinal Arrays of Compound Slots

Abstract: Abstract-The arrays of compound-slots (inclined and displaced from waveguide centre) are not so common in the literature and the existing systematic method of design does not take into account the presence of surrounding elements. For this kind of slots, the reasons why the Elliott's procedure cannot be applied are physically explained. A new method based on circuit theory and scattering matrices connection to include the effects of the external mutual coupling in compound slots arrays is presented in this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Fig. 11 is also qualitatively consistent with the fact that the brightest debris discs are only found around hosts with higher metallicities (see Moro-Martín et al 2015;Montesinos et al 2016). We note again that multi-fragment population synthesis may quantitatively change the results but we expect the positive trend between debris disc mass and [M/H] to remain true.…”
Section: Preliminary Comparison To Observationssupporting
confidence: 84%
See 1 more Smart Citation
“…Fig. 11 is also qualitatively consistent with the fact that the brightest debris discs are only found around hosts with higher metallicities (see Moro-Martín et al 2015;Montesinos et al 2016). We note again that multi-fragment population synthesis may quantitatively change the results but we expect the positive trend between debris disc mass and [M/H] to remain true.…”
Section: Preliminary Comparison To Observationssupporting
confidence: 84%
“…(v) We also found that our model predicts an increase in the mean mass of the debris disc with metallicity of the host star, as found by Gaspar, Rieke & Ballering (2016). Related to that correlation, if only the brightest (most massive) debris discs are considered, then this result predicts a lack of bright debris discs at low [M/H] environments, as found by Moro-Martín et al (2015); Montesinos et al (2016).…”
Section: Comparison To Observationsmentioning
confidence: 55%
“…In addition, some work showed that the analytical results in the case of considering the mutual coupling in the calculations of the slots excitations are very close to those resulting from CST simulation software 40,47,48 . Taking into account the mutual coupling effects, the radiation characteristics can be slightly enhanced in terms of the SLLs and return loss.…”
Section: Design Proceduresmentioning
confidence: 62%
“…24 In addition, some work showed that the analytical results in the case of considering the mutual coupling in the calculations of the slots excitations are very close to those resulting from CST simulation software. 40,47,48 Taking into account the mutual coupling effects, the radiation characteristics can be slightly enhanced in terms of the SLLs and return loss. In this work, we were able to achieve the desired SLL at the required resonance frequency, and hence any further enhancement that can result from including the mutual coupling effects in the design equations is not essential for the overall results.…”
Section: Mutual Coupling Between the Coupling And Radiating Slotsmentioning
confidence: 99%
“…A control of electrodynamic characteristics of the radiators and coupling slots can be realized, first of all, by varying slot geometric dimensions and positions relative to the waveguide walls under conditions that the coordinate system axes associated with the slot and waveguide are parallel. One of the ways to achieve required frequency-energy and spatial characteristics of slot radiators consists in varying an inclination angle of a longitudinal slot axis relative to coordinate waveguide axes [8][9][10][11][12]. In this case, the single slot cut in the waveguide end wall, in contrast to the one located on its side walls, can radiate up to 100% of the supplied power.…”
Section: Introductionmentioning
confidence: 99%